Teaching Practices of Mathematics Teachers in Selected Public and Private Elementary Schools - Jay Magno (Philippine Association of Institutions for Research, Inc., 2014)
Teaching practices comprise instructional teaching principles and methods. Instructional teaching method depends mostly to the skill and information that is found or influenced by the enthusiasm of the teacher. This study was conducted to determine teaching practices and problems encountered in the public and private elementary schools. Further, it sought to find out the following: a) mathematics teachers' socio-demographic profile; b) their usual teaching practices; c) the problems they encountered; d) the trainings they need; and e) the training plan for Mathematics teachers. Descriptive research design was used in the study. Data were collected from the 15 participants. They were the selected elementary Mathematics teachers. Survey questionnaire was utilized to find out the demographic profile for the teachers, the usual teaching practices, the problems encountered and the training needs assessment. The data gathered were summarized, translated, analyzed and matched with the result of the focus group discussion. It was found out that lack of more comprehensive trainings among teachers with the new trends of teaching methodologies and strategies and insufficient resources and funding; negative views about seminars and trainings and the scarcity of trainings conducted within their reach and capacity were revealed in both focus group discussion and in the results of the survey conducted. Based on the results, the design was formulated to address the problems as identified. The researcher recommends that school administrators should utilize the training design proposed.